2021
DOI: 10.1097/mot.0000000000000909
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparities in transplantation

Abstract: Purpose of review Transplantation is the life-saving therapy for patients suffering from end-organ failure, and as such, equitable access to transplantation (ATT) is of paramount importance. Unfortunately, gender/sex-based disparities exist, and despite the transplant community's awareness of this injustice, gender/sex-based disparities have persisted for more than two decades. Importantly, no legislation or allocation policy has addressed inequity in ATT that women disproportionately face. In fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 62 publications
1
23
0
Order By: Relevance
“…Women compose the majority of kidney donors worldwide ( 29 , 74 , 98 ). Living kidney donation is associated with surgical risk and the possibility of CKD in the long-term.…”
Section: Barriers To Living Donor Kidney Transplantmentioning
confidence: 99%
“…Women compose the majority of kidney donors worldwide ( 29 , 74 , 98 ). Living kidney donation is associated with surgical risk and the possibility of CKD in the long-term.…”
Section: Barriers To Living Donor Kidney Transplantmentioning
confidence: 99%
“…Their assumption was that older and sicker women were probably more likely misclassified (or they misclassified themselves) as too frail to undergo a kidney transplant. In contrast, Sheikh et al [25] demonstrated that women were more compliant and had equal or better outcomes after transplant than men. A study conducted in the US highlighted the fact that women undergoing haemodialysis were less likely than men to have discussions about kidney transplantation as a treatment option [19].…”
Section: Discussionmentioning
confidence: 91%
“…Exception points have been awarded to groups whose mortality is not reflected in the MELD-Na score, such as hepatocellular carcinoma (HCC) patients. Despite these strides, women have remained persistently disadvantaged in their access to LT. Women have had increased wait list mortality and lower transplant rates for several decades [2].…”
Section: Introductionmentioning
confidence: 99%
“…This disparity has largely been attributed to sex bias in the MELD allocation and exception point system as well as difficulties in donor and recipient size matching as a result of the smaller size of female recipients [2]. However, many studies demonstrate that gender inequity may be more complicated and nuanced than bias within the allocation system [3 ▪ ].…”
Section: Introductionmentioning
confidence: 99%